Comparative embryological study of some Jerusalem artichoke (Helianthus tuberosus L.) accessions with different seed-setting ability from the VIR collection - O. N. Voronova; A. A. Babro; A. V. Lyubchenko (Труды по прикладной ботанике, генетике и селекции)
Background. Jerusalem artichoke (Helianthus tuberosus L.) is a valuable agricultural plant, characterized by mostly vegetative propagation and depression of sexual process. This feature notably impedes breeding improvement of both Jerusalem artichoke and its hybrids with sunflower. That is why a detailed investigation of possible reasons for the failure of seed setting is very important for this crop.   Materials and methods. Jerusalem artichoke accessions from the VIR collection: cvs. ‘Topianka’ (k-70), ‘М-24-29’ (k-90), ‘2М-22-29’ (k-119), Skatovsky (k-123), and ‘Kievsky krasny’ (k-170), grown at Maikop Experiment Station of VIR, were examined. The material for embryological analysis was fixed at the stage of anthesis, processed, and analyzed at the Embryology and Reproductive Biology Lab of the Komarov Botanical Institute.   Results. A cytomorphological analysis of pollen grains and examination of anther walls and ovules with embryo sacs showed that from 51 to 95 % of the pollen grains and from 23.1 % to 66.6 % of the embryo sacs were formed normally. Abnormalities in female reproductive structures appeared more frequently but they did not determine the poor seed setting. Among the studied accessions, both cvs. ‘Kievsky krasny’, with the greatest number of abnormalities in male and female reproductive structures, and ‘Topianka’, with the smallest number, produced almost no seeds. The greatest number of seeds (from 207 to 1164) were set in ‘2M-22-29’, with the medium amount of normal generative structures, both male (pollen fertility was 81 %) and female ones (59,4 % of viable embryo sacs). Self-incompatibility observed in cv. ‘Topianka’ could cause the pollination failure, destruction of normal embryo sacs, and seed production decrease.   Conclusion. Thus, a combination of several factors (absence of developmental abnormalities in generative structures, crosspollination, and a compatible pollinizer) is necessary for successful seed setting in Jerusalem artichoke.